2019
DOI: 10.7150/jca.34016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HPV Infection on the Occurrence and Development of Laryngeal Cancer: A Review

Abstract: Laryngeal cancer has the second highest incidence of head and neck malignant tumors worldwide. In recent years, studies have shown that human papillomavirus (HPV) infection may be a high-risk factor for laryngeal cancer and closely related to the development and prognosis of laryngeal cancer. The mechanism of the occurrence and development of laryngeal cancer caused by HPV infection needs investigation, as does a rapid and effective HPV detection method for effectively preventing the occurrence of laryngeal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Head and neck malignant cancers take major responsibility for cancer-related mortality and morbidity, and its subset laryngeal cancer has the second-highest incidence and seriously threatens the life of patients 1,2. Patient-reported symptom questionnaires have noted that most laryngeal cancer patients experience voice, speech and swallowing afflictions, together with lowering quality of life and distress even after surgery or radiotherapy 3.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck malignant cancers take major responsibility for cancer-related mortality and morbidity, and its subset laryngeal cancer has the second-highest incidence and seriously threatens the life of patients 1,2. Patient-reported symptom questionnaires have noted that most laryngeal cancer patients experience voice, speech and swallowing afflictions, together with lowering quality of life and distress even after surgery or radiotherapy 3.…”
Section: Introductionmentioning
confidence: 99%
“…Besides smoking, drinking and air pollution, high-risk HPV (HR-HPV) infection was found to be one of the most important pathogenic factors of LC (30). Interestingly, HPV infection affects the LC tumorigenesis via genomic integration, activating proto-oncogenes and inhibiting anti-oncogenes, indicating that the genetic dysregulation and pathological factors may interplay each other and both promote the LC development (31).…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and progression of LC is a complicated process driven by various pathogenetic factors and dysregulation of multiple genes (3). Smoking and heavy alcohol consumption have been deemed to be the most significant risk factors for LC, and HPV infection, air pollution and sex hormone levels have also been considered as the risk factors for LC (4). With respect to dysregulated genes, accumulating studies have shown that the dysregulation of multiple genes contribute to the malignant progression of various tumors, especially LC (5).…”
Section: Introductionmentioning
confidence: 99%